THE EIGHT CHANNEL PHOTOMETER POLARIMETER 1. THE SELECTION AND REGISTRATION SYSTEM - Blagodyr, J. (Одеські астрономічні публікації, 2017)
This paper presents the selection and registration system of the eightchannels photometerpolarimeter, which was developed at the Lviv Astronomical observatory for observations of the artificial satellite of the Earth. As feeding optics are two Cassegren system telescopes with diameter 3500 mm and equivalent focus 3.5 m installed at the four-axes guidemounting. The device allowed to produce the measurements in UBV system to measure the degree of linear polarization and location of oscillations plane simultaneously in eight spatial-timing divided channels with automatically subtraction of background. The lights fluxes of each channels were registrated by four photomultipliers.The selection and registration system isthe separated block, which allowes to carry out primary working up the signals and to enter the resulting signals to the computer at the real time.